Transformation of Population Administration Services in Sidoarjo Regency - Mursyidah, Lailul; Choiriyah, Ilmi Usrotin; Agustina, Isna Fitria (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
Quality public services are one of the benchmarks for the success of government implementation. One of the public services which is a basic service for the community is population administration services. To ensure the implementation of improvements in the quality of population administration services efficiently and effectively, orderly population administration and increasing the scope of ownership of population documents as well as improving service performance, the Sidoarjo Regency Population and Civil Registration Service has carried out various innovations in services. The method used in this article is through literature study by exploring various sources including journals, books, official documents, digital data and official news limited by the author from 2018 to 2024. Transformation of population administration services carried out by the Population and Registration Service Sidoarjo Regency's civil services include the Peduli Dilan program in 2019, Plavon (Online Service) Dukcapil in 2021, and Integrated Ball Pick-up in 2022. The transformation of population administration services carried out by the Sidoarjo Regency Population and Civil Registration Service is able to create effective and effective services. Efficient and increasing ownership of population administration documents for the people of Sidoarjo Regency.